Tolcapone induces oxidative stress leading to apoptosis and inhibition of tumor growth in Neuroblastoma. (21st April 2017) - Maser, Tyler; Rich, Maria; Hayes, David; Zhao, Ping; Nagulapally, Abhinav B.; Bond, Jeffrey; Saulnier Sholler, Giselle
Abstract: Catechol‐O‐methyltransferase (COMT) is an enzyme that inactivates dopamine and other catecholamines by O‐methylation. Tolcapone, a drug commonly used in the treatment of Parkinson's disease, is a potent inhibitor of COMT and previous studies indicate that Tolcapone increases the bioavailability of dopamine in cells. In this study, we demonstrate that Tolcapone kills neuroblastoma (NB) cells in preclinical models by inhibition of COMT. Treating four established NB cells lines (SMS‐KCNR, SH‐SY5Y, BE(2)‐C, CHLA‐90) and two primary NB cell lines with Tolcapone for 48 h decreased cell viability in a dose‐dependent manner, with IncuCyte imaging and Western blotting indicating that cell death was due to caspase‐3‐mediated apoptosis. Tolcapone also increased ROS while simultaneously decreasing ATP‐per‐cell in NB cells. Additionally, COMT was inhibited by siRNA in NB cells and showed similar increases in apoptotic markers compared to Tolcapone. In vivo xenograft models displayed inhibition of tumor growth and a significant decrease in time‐to‐event in mice treated with Tolcapone compared to untreated mice. These results indicate that Tolcapone is cytotoxic to neuroblastoma cells and invite further studies into Tolcapone as a promising novel therapy for the treatment of neuroblastoma. Abstract : This manuscript reports a novel mechanism for targeting neuroblastoma through inhibition of catechol‐O‐methyltransferase with Tolcapone. This results in neuroblastoma cell death, increased intracellular reactive oxygen species levels, decreased ATP levels, and tumor inhibition in xenografts. This treatment provides promising preclinical results, which may be a potential novel treatment for neuroblastoma and is being tested in a Phase I study currently.